Tourists’ Satisfaction on Visiting Retro Market: A Case Study of TalatKoKloi (KoKloi Retro Market) at Muang District, Rayong Province, Thailand - Sripairoj, Quandee; Silanoi, La-iard (Journal of Cultural Approach, 2015)
The objective of this research is to study the tourists’ satisfaction on the 7Ps of the marketing mixed factors when visiting TalatKoKloi (KoKloi Retro Market), Muang District, Rayong Province, Thailand, according to the characteristic of the tourists. This study is the quantitative research which the questionnaires were used at the 384 sample size with 95% of level of confidence and the error is within .01 of the population standard deviation. The descriptive statistics used were frequency, percentage, mean and standard deviation and the inferential statistics used for comparing means were the t-test and One-way ANOVA which the Scheffeˊ Method was used for the multiple comparisons as well. The results of the study were that most tourists were Rayong residents, married, female, of approximately30-39 years old. Many of them were vocational or high school graduated, office personnel (with the monthly salary of about 10,000 to 19,000 baht), and preferred to travel during weekends. The tourists were satisfied most on the place (channels of distribution), people (staffs), process(service procedures), prices, physical evidence, and products and services, while the satisfaction on marketing promotions was regarded as adequate. The hypothesis test for the difference of the means was indicated that the tourists with different ages, marital status, occupations, and income be satisfied at the TalatKoKloi Retro Market differently at the 5% significance level; but for the tourists with different gender, educational level, duration of travels, and residences, there is no sufficient evidence to reject Ho: at the 5% significance level, that is, they do not have the different satisfaction at the TalatKoKloi Retro Market.